Linguistic Differences in the Past Indefinite Tense: A Comparative Study of Arabic and Urdu - Rani, Rabia (الدراسات الإسلامية, 2020)
The present paper presents grammatical analysis and comparison between Urdu and Arabic languages with special reference to the past indefinite tense in Arabic and Urdu. Linguistics entails scientific and structural study of a language whereas grammar is a core and fundamental aspect of the linguistics. The grammatical study among different languages is also a challenging subject of linguistics. The present research shows that in Arabic the subject affects the verb whereas in Urdu the object affects the verb. It also observes that the sequence of the sentence in both the languages is different. Since Arabic is an ancient language, it has diversified grammatical rules for each word. However, Urdu came into existence through a prolonged process of borrowing alphabets, words, and phrases from different languages.Grammatical rules of Arabic specifically have precedence over those of Urdu, as the former contains detailed rules of the dual case (muthannā), the rules of the subject, object, and prepositions. The article discusses grammatical differences and similarities. It also refers to the order of sentences in both the languages, as each language has a special order of sentences. Keywords Linguistics, Grammar, Arabic, Urdu, Structure, Past Tense